Electrical Impedance Tomography: Hardware Fundamentals And Medical Applications - Escobar Revelo, Fausto Andrés; Mosquera Leyton, Víctor Hugo; Rengifo Rodas, Carlos Felipe (Ingeniería Solidaria, 2020)
Introduction: The following article shows a systematic review of publications on hardware topologies used to capture and process electrical signals used in Electrical Impedance Tomography (EIT) in medical applications, as well topicality of the EIT in the field of biomedicine. This work is the product of the research project “Electrical impedance tomography based on mixed signal devices”, which took place at the University of Cauca during the period 2017-2019. Objective: This review describes the operation, topicality and clinical use of Electrical Impedance Tomography systems. Methodology: A systematic review was carried out in the IEEE-Xplore, ScienceDirect and Scopus databases. After the classification, 106 relevant articles were obtained on scientific studies of EIT systems; applications dedicated to the analysis of medical images. Conclusions: Impedance-based methods have a variety of medical applications as they allow for the reconstruction of a body region, by estimating the conductivity distribution inside the human body; this is without exposing the patient to the damaging effects of radiation and contrast elements. Impedance-based methods are therefore a very useful and versatile tool in the treatment of diseases such as: monitoring blood pressure, detection of atherosclerosis, localization of intracranial hemorrhages, determining bone density, among others. Originality: It describes the necessary components to design an EIT system, as well as the design characteristics depending on the pathology to be visualized.